Alternative modernities in the history of Iban popular music from 1950s to 1970s - Lim, Keh Nie (2019)
This thesis provides an in-depth study of the history of Iban popular music (1950s–1970s) by analyzing how alternative modernity is articulated through Iban popular songs. In exploring the potency of popular music, it uncovers the socio-cultural meanings of song lyrics and paradoxes of the largest indigenous ethnic group in Sarawak who experienced modernity from pre-modern to modern, the flux and agents of change from Brooke Rule to British colonialism to the Federation of Malaysia. Fundamentally, I argue that the establishment of Radio Sarawak and Iban Radio in the 1950s not only disseminated information to the people but also created a critical identity-forming space where the Ibans articulated modernity through the creation of their own popular music. Historically, the Iban is a cultural group located geographically and politically on the periphery of the multi-cultural nation of Malaysia. Building upon Bart Barendregt (2014) historiographic accounts of ‘alternative modernities’ in Southeast Asian popular music, this thesis examines how Iban culture bearers created popular music in the image of mainstream trends, but covertly expressed their socio-cultural and socio-political identity as emerging Sarawakians. Using historiographic approach, this methodology unravels the intricacies of the emergent creation of Iban popular music through an intertextual analysis of Iban popular music and its song lyrics. Drawing on narratives of music making experiences from the singers and songwriters themselves, the research collected sentiments and interpretations from culture bearers who shared anecdotes during interview sessions. This guided musical and historiographical analysis and literature surveys. Although Iban popular music is a genre appropriated by Western, Malay and Hindustani music forms, I argue that Iban popoular music articulated an alternative modernity for their socio-cultural and political history, allowing the Ibans to respond with a spirit of nationalism while simultaneously negotiating modernity in a new nation. They desired to transition and challenged themselves to be modern in a new landscape under the Federation of Malaysia. As with other ‘periphery ethnicities’ in Southeast Asia who were aspiring to be accepted in a new nation through popular music, the Ibans did not just conform to the mainstream industry but negotiated their own set of ideals, morals, values and traditions expressed in the Iban language and felt as a founding generation of Ibans who negotiated popular music in Sarawak.